Plan estratégico para el talento humano de la sucursal De Kimberly Clark del cantón Quito provincia de Pichincha - Romero Pinzón, Norma Elizabeth (2014)
Currently the world economic situation and the various social, cultural, political processes affect all levels and also to many of the companies facing the constant challenges of competition and technology, some of them are affected mostly; therefore, they are essential to use strategic plans that lead to the achievement of its objectives and seeks to be and have a better and greater participation in a market that is increasingly competitive. As well, for the business sector in the provision of their services especially the distribution and marketing of consumer products, companies in this study to put their best effort to offer their goods or services and market positioning. In our country the business is generating income and capital although this is not empowered enough to Ecuadorian households subsist in the best way. These activities are very characteristic marketers anywhere in the country. One thing that stands in our midst, consisting of permanent way of life especially for business. Commercial activity is also undertaken by large, medium and small businesses, as well as for micro-enterprises are worked on their own and as part of the urban informal sector. Loja still maintains a clear dependence on the foreign market in the supply of raw materials and technology; characterized by a large trade index and low level of productivity that makes our economy is weak and industrial backwardness is generated. Also considering the high inflation rate limiting to improving living conditions for companies and therefore of society. Given this critical situation for businesses and stay in the bitter struggle against the competition, this proposed project is aimed at the implementation of a Strategic Plan for Human Resource Branch of Kimberly Clark of Canton Quito. Exposing main objective achieved through the realization of this increased participation in the local market strategic plan. Also, to achieve this purpose the following compliments objectives: • Current Situation Analysis of Kimberly Clark Company for the Canton Quito as to show its position. • Perform SWOT Analysis. . The External factors gives a weight of 2.64, which means that the company has more opportunities and threats you can not do much damage, while Internal factors gives a weight of 2.64, which means the company has more strengths than weakness. • Develop a strategic plan for the Company Kimberly Clark of Canton Quito. This project was conducted in the city of Quito, in the "Company Kimberly Clark of Canton Quito", whose population sample of customers of the company is 774, consideration was given to a segmentation of 264 people surveyed. Surveys that allowed the completion of the thesis project titled "STRATEGIC PLAN FOR HUMAN TALENT BRANCH OF KIMBERLY CLARK OF CANTON QUITO province PICHINCHA" with the respective analysis of its current operation, in relation to their strengths and weaknesses, opportunities and threats, which also helped establish some alternative solutions. Thanks to the formulation of this thesis project, the formulation of specific and strategic objectives of management interest possible, exposed in the latter section of the PROPOSAL for Kimberly Clark Company of Canton Quito properly grounded in theoretical concepts for the realization of this plan. Where the different research techniques and the scientific method, were very important in achieving these goals and in the development of this study. In compliance with the regulations established by graduation from the National University of Loja.